Tingkat Keberdayaan Peserta Program Kecamatan Jati Agung Kabupaten Lampung Selatan - Pratiwi, Amalia Tyas Budi; Nurmayasari, Indah; Silviyanti, Serly; Nikmatullah, Dewangga (Suluh Pembangunan : Journal of Extension and Development, 2023)
The empowerment of farmers in the P2L Program is the output of the empowerment activities carried out. The empowerment process is carried out by involving the participation of farmers who are members of women farmers groups. The purpose of this research is to explain the level of empowerment of P2L participants in Jati Agung District. Researched was conducted in Jati Agung Sub-district. in March-June 2022. The respondents in this study amounted to 50 members group women farmers participating in the P2L Program in Jati Agung District. This research used survey method and the data were analyzed using quantitative descriptive. The results of the study are. the level of empowerment of the P2L Program participants, namely the level awareness and desire to change (power to) and skill to increase capacity to gain access (power within) is in the high category while the level of skills. dealing with obstacles (power over) and skill cooperation an solidarity (power with) P2L participants in Jati Agung District is still belongs to the medium category